STRUCTURAL PHASE TRANSITIONS IN NATROLITE AT HIGH PRESSURES - Belitskiy I.A.; Fursenko B.A.; Kholedeyev O.V.; Goryaynov S.V. (My University, 1987)
Data is presented on the behavior of natural natrolite Na 2Al 2Si 3O 10·2H 2O from the Kola Peninsula under hydrostatic pressures of up to 50 kbar at room temperature. We studied transparent colorless prismatic monocrystalline blocks measuring 100 to 300 μm on a side, bounded by the (110 and (1̄10) cleavage planes. The experiments were run in a high-pressure unit with diamond anvils [9], and the measurements were made by optical polarization microscopy, multichannel Raman microspectroscopy and X-ray diffraction. Experimental evidence indicates that the behavior of natrolite under pressure in penetrative and nonpenetrative media differed significantly. When natrolite was compressed in water, we found two reversible phase transitions: natrolite I → II at 7.5 kbar, and natrolite II → III at 12.5 kbar. The natrolite I → II structural transition under pressure is reflected in the Raman spectra obtained.